Validation and green profile assessment of a binary solvent liquid phase microextraction method for the determination of chlorbenside and fenobucarb in lake and wastewater samples by GC-MS - Chormey, Dotse Selali (SPRINGER HEIDELBERG, 2023)
This study reports a liquid phase microextraction method based on binary extraction solvents, which were used to preconcentrate chlorbenside and fenobucarb from aqueous samples for determination by gas chromatography mass spectrometry. Parameters including the type, ratio, and volume of binary solvents, disperser solvent type and volume, and vortex period were optimized systematically to achieve high enrichment for the analytes. The optimum conditions obtained were used to validate the method, and the detection limits calculated for chlorbenside (0.71 ng/mL) and fenobucarb (0.33 ng/mL) correlated to enrichment factors of 399- and 912-folds, respectively. The optimum method was applied to lake water and wastewater samples in spike recovery experiments, and the results obtained (96-104%) verified the method as accurate and applicable to the aqueous sample matrices. Matrix matching calibration method was used to boost the accuracy of quantifying the two analytes in the wastewater sample, which presented interference effects. Assessment of the method's green profile based on penalty points confirmed the method's compliance with green analytical chemistry.
Keywords: Analysis; Detection limit; Dispersive liquid-liquid microextraction; Pesticide; Preconcentration; TANDEM MASS-SPECTROMETRY; RESIDUE; PESTICIDES; PRODUCTS; Environmental Sciences & Ecology